A Repurposed Drug Screen for Compounds Regulating Aquaporin 5 Stability in Lung Epithelial Cells - John Villandre; John Villandre; Virginia White; Travis B. Lear; Travis B. Lear; Yanwen Chen; Ferhan Tuncer; Emily Vaiz; Beyza Tuncer; Karina Lockwood; Dan Camarco; Yuan Liu; et al. (Frontiers Media S.A., 2022)
Aquaporin 5 (AQP5) is expressed in several cell types in the lung and regulates water transport, which contributes to barrier function during injury and the composition of glandular secretions. Reduced AQP5 expression is associated with barrier dysfunction during acute lung injury, and strategies to enhance its expression are associated with favorable phenotypes. Thus, pharmacologically enhancing AQP5 expression could be beneficial. Here, we optimized a high-throughput assay designed to detect AQP5 abundance using a cell line stably expressing bioluminescent-tagged AQP5. We then screened a library of 1153 compounds composed of FDA-approved drugs for their effects on AQP5 abundance. We show compounds Niclosamide, Panobinostat, and Candesartan Celexitil increased AQP5 abundance, and show that Niclosamide has favorable cellular toxicity profiles. We determine that AQP5 levels are regulated in part by ubiquitination and proteasomal degradation in lung epithelial cells, and mechanistically Niclosamide increases AQP5 levels by reducing AQP5 ubiquitination and proteasomal degradation. Functionally, Niclosamide stabilized AQP5 levels in response to hypotonic stress, a stimulus known to reduce AQP5 levels. In complementary assays, Niclosamide increased endogenous AQP5 in both A549 cells and in primary, polarized human bronchial epithelial cells compared to control-treated cells. Further, we measured rapid cell volume changes in A549 cells in response to osmotic stress, an effect controlled by aquaporin channels. Niclosamide-treated A549 cell volume changes occurred more rapidly compared to control-treated cells, suggesting that increased Niclosamide-mediated increases in AQP5 expression affects functional water transport. Taken together, we describe a strategy to identify repurposed compounds for their effect on AQP5 protein abundance. We validated the effects of Niclosamide on endogenous AQP5 levels and in regulating cell-volume changes in response to tonicity changes. Our findings highlight a unique approach to screen for drug effects on protein abundance, and our workflow can be applied broadly to study compound effects on protein abundance in lung epithelial cells.